Taurine ameliorates stress-induced degeneration of the urinary bladder - ERCAN, FERİHA; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2007)
We studied the potential effects of taurine, a free radical scavenger, on chronic water avoidance stress (WAS)-induced degeneration of the mucosa of the urinary bladder in experimental rats. Wistar albino rats were exposed to WAS for 2 h/day, for 5 days (WAS group). Before exposing them to WAS, taurine (50 mg/kg) (WAS+taurine group) was injected intraperitonally into the animals. Samples of urinary bladder were then investigated by light and scanning electron microscopy. Lipid peroxidation and gluthathione levels were also measured in the urinary bladder. In the WAS-only group, inflammatory cell infiltration, increased number of mast cells in the mucosa and ulcerated areas were observed. In the WAS+taurine group, relatively normal urothelial topography with microvilli, moderate inflammatory cell infiltration and decreased numbers of mast cells in the mucosa were observed. The increased lipid peroxidation and decreased glutathione levels in WAS rats were reversed by taurine treatment. We conclude that taurine protects against WAS-induced oxidant urinary bladder injury, and thus may be a possible therapeutic agent against interstitial cystitis, the symptoms of which are aggravated by stress conditions. (c) 2006 Elsevier GmbH. All rights reserved.
Keywords: interstitial cystitis; mast cells; microscopy; rats; taurine; water avoidance; stress; INTERSTITIAL CYSTITIS; MAST-CELLS; IN-VITRO; RATS; ACTIVATION; BARRIER; KIDNEY; INJURY; VIVO